Why Indian men rebel?: Explaining armed rebellion in the northeastern states of India, 1970-2007 - Vadlamannati, Krishna Chaitanya (Journal of peace research, 2011)
Armed conflicts have been a permanent feature of the northeastern region since Indian independence. Surprisingly, relentless conflicts in this remote region of India have received little attention in the literature. Although some studies on conflicts in India have made important contributions to understanding and analyzing the causes of conflicts in general, none of them has paid specific attention to the ongoing conflicts in the northeastern region of India. Relative deprivation and persistent economic and political discrimination are often identified as the major causes for armed rebellion in this region. I provide a first quantitative test of this argument, exploring whether deprivation and continual economic and political discrimination explain the probability of armed conflict incidence across nine northeastern states of India during the period 1970?2007. The main findings from probit estimations show that poverty (relative to the rest of the country) and economic and political discrimination explain conflict outbreaks, after controlling for income, population pressures, state capacity, ethnic affiliations, forest area, peace years, neighboring conflict incidence, and distance to New Delhi. The study also reports considerable support for the baseline results when controlling for potential reverse feedback effects using the generalized method of moments. These results are robust to alternative estimation techniques and sample size.